Estimulando a coleta seletiva através da gamificação e tecnologia - Brandão, Ezequiel Sidney de Aguiar (Brasil, 2024)
Currently, due to the culture of industrialized products consumption, human beings end up producing, on average, just over 1 kg of solid waste per day. A large part of this waste is made up of materials that, through proper disposal, could be put back into the production cycle. However, the amount of residuum waste disposed of responsibly is far from ideal, generating sanitation problems in cities. This work proposes to develop a digital system that, using the gamification strategy, attracts attention, raises awareness and encourages many sectors of the society to actively participate in the process of disposal and selective waste collection in the city of Manaus. We will present here this system implementation, its modules, its versions in a Web and Mobile environment, in addition to the communication between such environments carried out through a Web Service REST.